2000
DOI: 10.1105/tpc.12.11.2283
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control and Evolution of Sesquiterpene Biosynthesis in Lycopersicon esculentum and L. hirsutum

Abstract: Segregation analysis between Lysopersicon esculentum (cultivated tomato) and L. hirsutum (wild form) in conjunction with positional verification by using near-isogenic lines demonstrated that biosynthesis of two structurally different classes of sesquiterpenes in these species is controlled by loci on two different chromosomes. A locus on chromosome 6, Sesquiterpene synthase1 ( Sst1 ), was identified for which the L. esculentum allele is associated with the biosynthesis of ␤ -caryophyllene and ␣ -humulene. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 26 publications
2
60
0
1
Order By: Relevance
“…Based on previous work, ␦-elemene is probably a decay product of germacrene C produced under elevated temperature of the GC inlet (23). Previous reports indicated that two sesquiterpene synthases genes on chromosome 6, designated SSTLE1 and SSTLE2, are responsible for the synthesis of sesquiterpenes in type VI glands (20,21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous work, ␦-elemene is probably a decay product of germacrene C produced under elevated temperature of the GC inlet (23). Previous reports indicated that two sesquiterpene synthases genes on chromosome 6, designated SSTLE1 and SSTLE2, are responsible for the synthesis of sesquiterpenes in type VI glands (20,21).…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports indicated that trichomes on the surface of tomato leaves, stems, and green fruit produce monoterpenes and sesquiterpenes (16,(19)(20)(21). We analyzed terpene content by using gas chromatography-mass spectrometry (GC-MS) in leaf trichomes by briefly dipping detached leaflets in tert-butyl methyl ether (MTBE).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes encoding terpene synthases might actually be expected to have more rapid rates of sequence divergence than other genes if secondary metabolism is under selection for increasing diversity. In this regard, gene duplication can be seen as an evolutionary process that can make an important contribution to generating diversity in terpene biosynthesis (Facchini and Chappell, 1992;Van der Hoeven et al, 2000;Aubourg et al, 2002). Many other genes of secondary metabolism also appear to have arisen from tandem duplication events (e.g., Pichersky and Gang, 2000;Kliebenstein et al, 2001;Kroymann et al, 2001;Reintanz et al, 2001;Clauss and Mitchell-Olds, 2003).…”
Section: Gene Duplication and Multiple Alleles Contribute To Terpene mentioning
confidence: 99%
“…Furthermore, a number of sesquiterpenes such as δ-elemene have been found to increase in the headspace of tomato plants with T. absoluta eggs (Anstasaki et al, 2015). However, these compounds are reported to play a role in tomato resistance against insects other than T. absoluta (Van der Hoeven et al, 2000;Bleeker et al, 2009). The production of such compound is aggravated when the environmental conditions are changed.…”
Section: Host Plant Selection Mechanism and Life Cycle Of T Absolutamentioning
confidence: 99%